Sintilimab plus bevacizumab biosimilar IBI305 and chemotherapy for patients with EGFR-mutated non-squamous non-small-cell lung cancer who progressed on EGFR tyrosine-kinase inhibitor therapy (ORIENT-31): first interim results from a randomised, double-blind, multicentre, phase 3 trial. Issue 9 (September 2022) - Lu, Shun; Wu, Lin; Jian, Hong; Chen, Ying; Wang, Qiming; Fang, Jian; Wang, Ziping; Hu, Yanping; Sun, Meili; Han, Liang; Miao, Liyun; Ding, Cuimin; et al.
Summary: Background: VEGF inhibitors can enhance the efficacy of immunotherapy. However, despite high initial response rates, almost all patients eventually develop treatment resistance to EGFR tyrosine-kinase inhibitors. We aimed to evaluate the efficacy and safety of sintilimab with or without IBI305 plus pemetrexed and cisplatin, compared with pemetrexed and cisplatin alone, for the treatment of patients with locally advanced or metastatic EGFR -mutated non-small-cell lung cancer (NSCLC) who had disease progression after receiving EGFR tyrosine-kinase inhibitor therapy. Methods: This randomised, double-blind, multicentre, phase 3 trial was conducted at 52 hospitals in China. Eligible participants were adults aged 18–75 years with locally advanced or metastatic NSCLC and EGFR mut who progressed after receiving a EGFR tyrosine-kinase inhibitor, had an Eastern Cooperative Oncology Group performance status of 0 or 1 with at least one measurable lesion, and an estimated life expectancy of at least 3 months. Participants were randomly assigned (1:1:1) to receive sintilimab (200 mg) plus IBI305 (15 mg/kg) plus pemetrexed (500 mg/m 2 ) and cisplatin (75 mg/m 2 ), sintilimab plus pemetrexed and cisplatin, or pemetrexed and cisplatin (chemotherapy alone) using block randomisation with stratification according to sex and presence or absence of brain metastases. All study drugs were administered intravenously on day 1 of each cycle, once every 3 weeks. Except for cisplatin, which was only given in the first four cycles, treatment was given for 24 months or until disease progression, intolerable toxic effects, withdrawal of consent, death, or other protocol-specified conditions, whichever occurred first. The primary endpoint was progression-free survival in the intention-to-treat population. We herein report the first planned interim analysis, with progression-free survival results for the comparison between sintilimab plus IBI305 plus chemotherapy versus chemotherapy alone. The progression-free survival results for the sintilimab plus pemetrexed and cisplatin group are immature and not reported here. This study is registered with ClinicalTrials.gov, NCT03802240 (recruiting). Findings: Between July 11, 2019, and July 31, 2021, 936 patients were screened and 444 were randomly assigned (148 to the sintilimab plus IBI305 plus chemotherapy group, 145 to the sintilimab plus chemotherapy group, and 151 to the chemotherapy alone group). Data cutoff for this interim analysis was July 31, 2021. After a median follow-up of 9·8 months (IQR 4·4–13·3), progression-free survival was significantly longer in the sintilimab plus IBI305 plus chemotherapy group versus the chemotherapy alone group (median 6·9 months [95% CI 6·0–9.3] vs 4·3 months [4·1–5·4]; hazard ratio 0·46 [0·34–0·64]; p<0·0001). The most common grade 3 or 4 treatment-related adverse events were decreased neutrophil count (30 [20%] in the sintilimab plus IBI305 plus chemotherapy group vs 26 [18%] in the sintilimab plus chemotherapy group vs 27 [18%] in the chemotherapy alone group), decreased white blood cell count (17 [11%] vs 12 [8%] vs 13 [9%]), and anaemia (18 [12%] vs ten [7%] vs 15 [10%]). Potentially treatment-related deaths occurred in six patients (intestinal obstruction, gastrointestinal haemorrhage, and myelosuppression in one patient each, and three deaths of unknown cause) in the sintilimab plus IBI305 plus chemotherapy group, and in one patient in the chemotherapy alone group (unknown cause). Interpretation: In this interim analysis, sintilimab plus IBI305 plus cisplatin and pemetrexed was generally efficacious and well tolerated in patients with EGFR -mutated NSCLC who progressed after receiving EGFR tyrosine-kinase inhibitor therapy. Funding: Innovent Biologics and the National Natural Science Foundation of China. Translation: For the Chinese translation of the abstract see Supplementary Materials section.